SIMULATION OF CHEMICAL ACCIDENTS WITH ACETYLENE IN „MESSER TEHNOGAS“ KRALJEVO PLANT BY „ALOHA“ SOFTWARE PROGRAM - Ilić Komatina, Danijela; Galjak, Jovana; Belošević, Svetlana (Bulletin of Natural Sciences Research, 2018)
Chemical plants are generally associated with potentially high risk of chemical accidents. During chemical accidents hazardous substances jeopardize human lives, destroy material assests and degrade natural environment. The release of flammable and explosive gases or liquids especially poses a significant threat to the environment. This paper introduces the simulation of a chemical accident caused by an uncontrolled acetylene cylinder release in the warehouse of Messer Tehnogas Kraljevo chemical plant. The simulation was performed by ALOHA program package which defines a possible accident development and determines threat and safety zones. The assessment of potential scenarios is based on physico-chemical properties of the substance causing the accident. This paper discusses accident situations occurring under the most unfavorable atmospheric conditions.
Keywords: Hazardous substances; Acetylene; Chemical accident; Simulations; Releaser; Messer Tehnogas Kraljevo; “ALOHA” software